Description of a new species of Uroballus Simon, 1902 (Araneae: Salticidae) from Malaysia, with the longest spinnerets of any known jumping spider - Logunov, Dmitri V. (Zootaxa, 2014)
A new species Uroballus koponeni sp. n. (♀) from Malaysia (Borneo) is diagnosed, illustrated and described. The genus is unusual for jumping spiders in having extremely long spinnerets.